2020
DOI: 10.2807/1560-7917.es.2020.25.46.1900629
|View full text |Cite
|
Sign up to set email alerts
|

Characterising West Nile virus epidemiology in Israel using a transmission suitability index

Abstract: Background Climate is a major factor in the epidemiology of West Nile virus (WNV), a pathogen increasingly pervasive worldwide. Cases increased during 2018 in Israel, the United States and Europe. Aim We set to retrospectively understand the spatial and temporal determinants of WNV transmission in Israel, as a case study for the possible effects of climate on virus spread. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…Figures 4A to 4C). This output showed that, in accordance to previously described geo-temporal patterns for other mosquito-borne viruses [34] and WNV [41] in different countries, natural climate variations strongly influence both inter-and intra-yearly variation in transmission potential. When quantifying the number of months within a year for which the estimated transmission potential was not zero, we again found a clear division between the north and south ( Figures 4BDFH).…”
Section: Figure 3 -Monthly Revive Culex Pipiens Counts In Portugal Vesupporting
confidence: 87%
See 2 more Smart Citations
“…Figures 4A to 4C). This output showed that, in accordance to previously described geo-temporal patterns for other mosquito-borne viruses [34] and WNV [41] in different countries, natural climate variations strongly influence both inter-and intra-yearly variation in transmission potential. When quantifying the number of months within a year for which the estimated transmission potential was not zero, we again found a clear division between the north and south ( Figures 4BDFH).…”
Section: Figure 3 -Monthly Revive Culex Pipiens Counts In Portugal Vesupporting
confidence: 87%
“…This index is the theoretical transmission potential P of each adult female mosquito in the zoonotic reservoir (derived from the decomposition of R 0 =MP). P can be interpreted as a proxy for the risk of spillover to the human and equine populations (as demonstrated recently for Israel [41]).…”
Section: West Nile Virus Transmission Potential In Portugalmentioning
confidence: 86%
See 1 more Smart Citation
“…The annual fluctuations in WNV activity can be influenced by several factors. In the current issue of Eurosurveillance, Lourenço et al have analysed West Nile virus epidemiology in Israel [15]. WNV infections caused by diverse strains have been diagnosed in the country in the past decade.…”
mentioning
confidence: 99%
“…To estimate the transmission potential of WNV we calculated the index P, a computational approach informed by climatic variables from Lourenço et al recently applied in Israel [14] ( see Technical Appendix for detail ). In the 2015-2016 season, cases in Piauí presented a seasonal signal typical of WNV and other mosquito-borne viruses, with a peak between February and May (late summer and autumn).…”
Section: Textmentioning
confidence: 99%